CHANGES IN BIOCHEMICAL CONSTITUTION OF RADISH (Raphanus sativus L.) UNDER COPPER TOXICITY - P. Vijayarengan, M. Christhuuthayam,; M. Maheswari, A. Natarajan, (Journal of Plant Stress Physiology)
The effect of copper stress on the biochemical content of Raphanussativus L.were studied. The plants were grown in pots containing the soil with different concentrations of copper (0, 50, 100, 150,200 and 250 mg kg-1). Five replicates were maintained for each level. Biochemical contents such as total sugar, starch, amino acid, proline and protein) contents were analyzed on 45th day. Biochemical contents such as total sugar, starch, amino acid and protein were increased in low level of copper (50 mg kg-1) and decreased in high level of copper in the soil (100-250 mg kg-1). But the proline content increased in high level of copper in the soil (100-250 mg kg -1) when compared to control and 50 mg kg-1.